If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = -12 + n Solving 5 = -12 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 5 + -1n = -12 + n + -1n Combine like terms: n + -1n = 0 5 + -1n = -12 + 0 5 + -1n = -12 Add '-5' to each side of the equation. 5 + -5 + -1n = -12 + -5 Combine like terms: 5 + -5 = 0 0 + -1n = -12 + -5 -1n = -12 + -5 Combine like terms: -12 + -5 = -17 -1n = -17 Divide each side by '-1'. n = 17 Simplifying n = 17
| 21x-27=22x+29 | | 3(2x+5)-x=2x+15 | | 3=6p-21 | | -317+14x=147-2x | | 12=k-5 | | 15=r+5 | | 6u=-48 | | -(-3-2x)-5= | | -35-14x=21-16x | | 10x^2-16x-6=0 | | 5x+17y=91 | | (-2i)(-8i)(2)= | | 4-6x=x+11 | | -56+24=22x+22 | | 15=2(5m+10)+3(5-4m) | | n-17=-18 | | -10(-9+x)=190 | | -116-14=-7x+213 | | (2x^2)-7y^2=-13 | | 5(5n+9)+2= | | b+42=19 | | -129+20x=12x+207 | | 11m=-110 | | 5a-4a+2b-4= | | -16x=272 | | 6(v+4)-2v=2(2v+3)-9 | | X-10y=12 | | -177+5x=299+19x | | b-9=3 | | 3(x-2)=3(x+4) | | 3(7p-1)-6= | | -22x-51=61-18x |